Prediction of preeclampsia by a combination of maternal spot urinary protein-creatinine ratio and uterine artery doppler - Modak, Rupali; Pal, Amitrajit; Pal, Amitava; Ghosh, Mrinal K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Preeclampsia (PE) is heterogeneous disorder. The aim of the study was to observe the role of a spot urinary protein - creatinine ratio (UPCR) and uterine artery doppler velocimetry measured between 20-24 weeks of gestation in prediction of preeclampsia. Methods: Prospective observational study conducted on 120 pregnant mothers with singleton pregnancy between 20-24 weeks of gestational age in two tertiary teaching hospitals in eastern India. A spot urinary protein creatinine ratio (UPCR) was determined in a mid- stream urine sample and estimation of protein was done by immunoturbidimetric micro albumin method and creatinine by modified Jaffe’s method. Doppler velocimetry was also determined at 20-24 weeks of gestation. A notch in uterine artery, unilateral or bilateral; or RI > 0.7 and PI of > 1.45 were considered to have an abnormal result. Women were followed-up and relationship between variables was assessed by Chi- square test. Results: Women who subsequently developed preeclampsia had significantly higher UPCR (median 44.8 mg/mmol) when compared with women of unaffected groups (median 26.6 mg/mmol). The optimum spot urinary UPCR to predict preeclampsia was 35.5 mg/mmol and the cut-off value >35.5 mg/mmol had a test sensitivity (80%), specificity (94.06%), PPV (66.76%) and NPV (96.94%).The area under curve (AUC) of spot UPCR in ROC curve was 0.949 (95% CI,0.891 - 1.000). For predicting preeclampsia, the mean uterine artery RI had to be >0.7 having sensitivity (60%), specificity (97.03%), PPV (75%) and NPV (94.23%). The area under curve (AUC) was 0.856 (95% CI, 0.742 - 0.971). Conclusions: Second trimester UA doppler is a useful screening test for prediction of preeclampsia. This test works best when combined with a spot UPCR and accuracy of both the methods for prediction of preeclampsia was 92.24%.